O papel da ferrovia Santos - Iquique na integração da América Latina e no comércio com a Ásia - Reis, Alfredo Teodoro (2007)
All Brazilian evolution happened, one way or another, in the Atlantic Ocean. Everything began with the slave ships, in a triangle that seemed to be Brazil Portugal Africa and that, with time; eventually became Brazil England Africa. Since then, all development happens on the coast, the inner lands were left behind. The economic concentration on the east coast became even more clear with the growth of the American economy, in the XX century. It came to the point that, one of the planet s biggest wealth the Amazon forest is practically abandoned throughout these five hundred years. Our beautiful coast created in us, Brazilians, an intrinsic cultural difficulty we don t know what happens right there on the Pacific Ocean. Due to its gigantism, due to its natural resources which are considered endless, Brazil, even committing errors, even consenting losses, became a leader. Leader of a poor South America, nevertheless it is also naturally rich, our sister, our people and land, our brothers. Due to their even bigger difficulties, due to their freedom being obtained through sword and blood, full of resentment and differences, our brothers, Colombians, Ecuadorians, Peruvians, Bolivians e Paraguayans could not reach the same Brazilian development. In this way, it was created, throughout these 500 years, a death frontier on the West, that isolates us from the Asian development process. Chile, the Latin tiger , more similar to Hong Kong than to Brazil, that should be the gateway to Asia, due to its fantastic coast, is the clog, the fetter. If not, how to explain the isolation, the forgetfulness of its neighbors and brothers? While in the United States, the Anglo-Saxon entrepreneurship united two oceans with trains in 1880, Brazil was sleeping on a splendid cradle. The bi-oceanic junction Santos Iquique is a current and innovative idea and, considering all alternatives, it is an economically viable option to unite the South American people in order to reach the global markets